2018
DOI: 10.1097/md.0000000000009721
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fear of falling and associated factors among Japanese community-dwelling older adults

Abstract: To determine the prevalence of fear of falling and associated factors among Japanese community-dwelling older adults.Cross-sectional study between 2011 and 2013.Community in which residents voluntarily attended a health examination.We recruited 844 older adults (male, n = 350; female, n = 494) aged 60 to 92 years from among those who presented at the health examination.We assessed fear of falling, falls in the previous year, pain, comorbidity, and cataracts. Five times chair stand time was applied as an indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 35 publications
(54 reference statements)
4
51
3
7
Order By: Relevance
“…In others’ studies, “high concern” prevalence among older Brazilians has ranged from 51.9% to 95.2% (Cruz, Duque, & Leite, ; Malini et al, ; Moreira et al, ). However, other studies from India, Japan and Italy contradict our findings, with lower prevalence of FOF that ranged from 33.2% to 50% (Deshpande et al, ; Mane, Sanjana, Patil, & Sriniwas, ; Tomita et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…In others’ studies, “high concern” prevalence among older Brazilians has ranged from 51.9% to 95.2% (Cruz, Duque, & Leite, ; Malini et al, ; Moreira et al, ). However, other studies from India, Japan and Italy contradict our findings, with lower prevalence of FOF that ranged from 33.2% to 50% (Deshpande et al, ; Mane, Sanjana, Patil, & Sriniwas, ; Tomita et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…The difference in frequency may also be caused by recall bias based on retrospective data collection or the use of different assessment tools. Older people's fear of falling frequency is between 43.3% and 86% . A study conducted in the Netherlands with people aged 80 or over found a rate of fear of falling of 65.6% .…”
Section: Discussionmentioning
confidence: 99%
“…Older people's fear of falling frequency is between 43.3% and 86%. 17,20,26 A study conducted in the Netherlands with people aged 80 or over found a rate of fear of falling of 65.6%. 27 The fall frequency found by our study is higher than those of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, it analyzes the following activities: control of the intestine, bladder, personal hygiene, transfer of hygiene, transfer of bathtub, food, clothing, transport of wheelchair to bed, walk and go up and down stairs. The total score can range from zero (dependent) to 100 (fully independent) (9)(10) . For Portuguese, the use of this scale was validated in the context of outpatient care, with a reliability of 0.88 (28) , although not associated to the study of diaper use.…”
Section: Discussionmentioning
confidence: 99%
“…Another system that evaluates the independence in the execution of activities is the Care Ensure System, not yet translated or validated into Portuguese; it evaluates the need for toilet assistance, including removal of clothing and cleaning of the skin area in contact with the diapers. The levels of necessary care punctuated in this instrument include: level 2 for moderate care; level 3, significant care; level 4, intensive care; and level 5, the maximum care (10) .…”
Section: Discussionmentioning
confidence: 99%